Music and the Twentieth Century: The Periodical Moment of Philosophical Dissension (Journal of Philosophy Culture and Political Science, 2018)
This article is devoted to the analysis of social, culturaland technical conditions of the evolution of musicalphenomena in ХХ century in some music theoretical andphilosophical respects.